Effect of spacer type and cold compaction pressure on structural and mechanical properties of porous titanium scaffold. (April 2015) - Khodaei, M.; Meratian, M.; Savabi, O.
Abstract : Cell shape plays a crucial role on mechanical properties of titanium foam as scaffold in bone tissue engineering. In the present research, titanium foam was prepared using space holder technique. Sodium chloride and ammonium bicarbonate were utilised as spacer agent separately. The effect of cold compaction pressure and spacer agent type on the cell morphology was investigated by scanning electron microscopy (SEM) and optical stereo microscopy. Image analysing technique was performed to evaluate the microscopic images quantitatively. Exact salt leaching time was introduced by a new approach using electrical conductivity measurement. True and apparent porosities and compressive mechanical properties of the synthesised foams were evaluated. Finally, the superior spacer agent and appropriate cold compaction pressure were determined. It was shown that sodium chloride, due to maintaining its morphology during cold compaction pressure and absence of chemical side effects on titanium, is the superior spacer agent.